Bakteri Penyebab Infeksi Nosokomial Pada Alat Kesehatan dan Udara di Ruang Unit Gawat Darurat RSUD Abepura, Kota Jayapura - Herlando Sinaga; Dirk Y.P. Runtuboi; Lisye I. Zebua (Jurnal Biologi Papua, 2014)
Nosocomial infection is a health care problem in hospital worldwide. Problem, that appeared may aggravate existing disease, even cause death. Nosocomial infection can be defined as an infection acquired or occurring in hospital. The aimed of study was to determinespecies of bacteria causing nosocomial infection on medical equipment and air sampling in Accident and Emergency Room  at Jayapura Hospital. This research was conducted at the Regional Health Laboratory (LABKESDA) Jayapura. The result showed that there were 13 species of bacteria found and there were 5 species of Staphylococcus cohnii, Klebsiella spp., Serratia marcescens, Staphylococcus haemolyticus, and Streptococcus spp.in the medical equipments at Emergency Room. Moreover, in air sampling of emergency room was founded 13 species of bacteria namely Staphylococcus haemolyticus (14%), Klebsiella spp (12%), Ser. marcescens (12%), E. Coli (12%), Sta. aureus (11%), Streptococcus spp (11%), Citrobacter sp (8%), Enterobacter  cloacae (8%), Sta. cohnii (4%), Pneumococcus 2%), Proteus spp. (2%), Sta. epidermidis (2%), and Sta. warneri (2%).Key words: Nosocomial infections, health equipments, air, hospital.